Penyuluhan Pengenalan Makanan Bergizi Dan Bernutrisi - Melati Yulia Kusumastuti; Cut Fatimah; Muhammad Gunawan; Pebrinawanti Br Saragih; Dyan Imelda; Sellyana Sitio; Sri Wahyuningsih (STIKES Columbia Asia Medan, 2025)
Bingkat Village is one of the villages located in Pegajahan District, Serdang Bedagai Regency, North Sumatra Province, with an area of 5.95 km2 or 595.96 hectares divided into 10 hamlets. Most of the land area in Bingkat Village is used as rice fields, which is 60.740% of the total land area and is used as fields and plantations of 26.830% of the total land area, so that the majority of heads of families in Bingkat Village are farmers. Healthy food is food that contains balanced nutrition, contains fiber and substances needed by the body for the child's growth and development process. Balanced nutrition can be useful as an energy substance, a regulator, and a building substance. Food also greatly affects children's digestion, so parents must be able to provide healthy food that can maintain children's digestion. So that it does not interfere with children's growth. Healthy food for digestion should be rich in nutritional elements such as carbohydrates, proteins, minerals, vitamins, and a little unsaturated fat, or more precisely abbreviated as the 4 healthy 5 perfect menu. Through this program by conveying about consuming Good and Healthy Nutritional and Nutritious Food. So that the community will avoid mistakes in choosing food and the negative impacts that may arise. The type of research used is quantitative descriptive research on survey methods through interviews.. Based on the results of research that has been conducted in Bingkat Village with a total of 19 respondents, 72% know about choosing nutritious and nutritious food and 28% know about food additives (BTM), then the level of community knowledge about nutritious and nutritious food is higher compared to the level of community knowledge about food additives (BTM).